Cardiac Memory T Waves After Termination of Fascicular Ventricular Tachycardia in the Emergency Room - Kara, Suleyman Cihan; Canpolat, Uğur (European Journal of Therapeutics, 2024)
Left posterior fascicular tachycardia (LPFVT) is a common type of idiopathic ventricular tachycardia that might be misdiagnosed as supraventricular tachycardia. Memory T wave is an inverted T wave that is seen after altered depolarization states such as pacemaker rhythm, ablated accessory pathways, ventricular tachycardia, or intermittent bundle branch blocks. Herein, we presented a young male patient who was admitted to the emergency room with FVT. After termination of tachycardia negative T waves (memory T wave) were seen. Memory T waves might be seen after the termination of FVT and must be differentiated from other causes of inverted T waves such as ischemia.